2020
DOI: 10.1111/1471-0528.16303
|View full text |Cite
|
Sign up to set email alerts
|

Interpregnancy interval and risk of perinatal death: a systematic review and meta‐analysis

Abstract: Background Interpregnancy interval (IPI) <6 months is a potentially modifiable risk factor for adverse perinatal health outcomes. Objective This systematic review evaluated the international literature on the risk of perinatal death associated with IPI. Search strategy Two independent reviewers screened titles and abstracts identified in MEDLINE, EMBASE and Scopus from inception to 4 April 2019 (Prospero Registration #CRD42018092792). Selection criteria Studies were included if they provided a description of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Compared with the IPI of 18-23 months, the IPI less than 6 months after delivery was the risk factor of adverse perinatal outcomes in the next pregnancy and increased the risks of preterm birth, very preterm birth, low birth weight, small for gestational age infants, offspring death, congenital abnormality, and NICU. The previous metaanalysis showed that short IPI was associated with increased risk of preterm birth, extreme preterm birth, low birth weight, and small for gestational age (4, 6, 51), and short IPI after live birth was related to perinatal death (9), which was accordance with our research results. In recent years, it has been found that the mechanism of adverse pregnancy outcomes caused by short IPI after delivery could be attributed to the comprehensive influence of factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Compared with the IPI of 18-23 months, the IPI less than 6 months after delivery was the risk factor of adverse perinatal outcomes in the next pregnancy and increased the risks of preterm birth, very preterm birth, low birth weight, small for gestational age infants, offspring death, congenital abnormality, and NICU. The previous metaanalysis showed that short IPI was associated with increased risk of preterm birth, extreme preterm birth, low birth weight, and small for gestational age (4, 6, 51), and short IPI after live birth was related to perinatal death (9), which was accordance with our research results. In recent years, it has been found that the mechanism of adverse pregnancy outcomes caused by short IPI after delivery could be attributed to the comprehensive influence of factors.…”
Section: Discussionsupporting
confidence: 93%
“…The most recent meta-analysis on the effects of short gestation intervals on fetal and maternal outcomes was published in 2012 ( 6 ), which was 10 years old and lacked research from some countries, such as China. Previous systematic reviews and meta-analyses have examined the influence of short IPIs on perinatal mortality outcomes, but the researchers compared the IPI < 6 months with IPI ≥ 6 months and calculated the combined effect values, so these researches could limit the results ( 9 ). Through meta-analysis, this study discussed the influence of short IPI on adverse pregnancy outcomes and provided a basis and guidance for women of childbearing age to choose the appropriate IPI.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating of patients who had a stillbirth revealed that the main reason was the preterm deliveries, placental abruption, and fetal anomaly. Contemporary studies revealed that women with an IPI of 6 months, which was approximately 12 months of IDI, were at risk of stillbirth ( 28 , 29 ) . However, contrary to these studies, Stephansson et al ( 30 ) stated that short IPI was not associated with stillbirth after adjusting the maternal characteristics and previous pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of mechanisms, a short IPI is known to be associated with increased transfusion risk ( 11 ) and adverse neonatal outcomes ( 1 , 37 , 38 ). The consensus remains that a short IPI is associated with adverse perinatal outcomes, especially in low-income settings ( 4 , 34 , 39 ). Preconception health status and SMM risk associated with a long IPI may also require more attention in maternity care.…”
Section: Discussionmentioning
confidence: 99%